Wedge Politics: Mapping Voter Attitudes to Asylum Seekers Using Large‐Scale Data During the Australian 2013 Federal Election Campaign. Issue 4 (29th August 2016) - Carson, Andrea; Dufresne, Yannick; Martin, Aaron
Abstract : This article examines Australian voters' responses to asylum seeker boat arrivals during the most recent 2013 federal election campaign. We explore this issue using a mixed‐methods approach, by conducting media monitoring analytics, content analysis of Liberal Party press releases, and statistical analysis of Voting Engagement Application data. We identify the salience of the issue to the public and the media and examine the prominence of this issue in Liberal Party political messaging about asylum seekers. We then analyze voters' attitudes to asylum seeker boat arrivals using Vox Pop Labs' Vote Compass data (n = 438, 050). The survey is of unprecedented size in Australia and contains information collected during the election campaign about citizens' attitudes to policy issues, enabling fine‐grained analyses of voter attitudes at the electorate and subgroup level. We find voters' attitudes toward asylum seekers, particularly in marginal electorates, impacted on vote intention. This effect is stronger among subgroup voters who care the most about that issue. These results suggest that the increase in the salience of the asylum seeker issue favored the winning Liberal Party.